A Study on Bengali Culture and It's Various Aspects: Exploring the Cultural Richness of West Bengal (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A standout amongst the most socially prosperous conditions of India, West Bengal is loaded up with amazements. Be it the distinctive religions all absorbing into one or the beautiful social occasions that appear to make up the magnificent express that it is. There is significantly more to West Bengal than enormous red bindis and dhoti kurtas. There are great deals of components about the culture of West Bengal, and now we will examine a portion of its fascinating parts. West Bengal has a rich heritage of astonishing literature with extraordinary creators like Sharat Chandra Chattopadhyay, Rabindranath Tagore, Kazi Nazrul Islam and Bankim Chandra Chattopadhyay contributing a considerable amount to the Bengali literature and also to the world literature.